2019
DOI: 10.3389/fendo.2019.00052
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Autophagy Influences the Function and Survival of Human Pancreatic Beta Cells Under Endoplasmic Reticulum Stress Conditions and in Type 2 Diabetes

Abstract: Autophagy is the major mechanism involved in degradation and recycling of intracellular components, and its alterations have been proposed to cause beta cell dysfunction. In this study, we explored the effects of autophagy modulation in human islets under conditions associated to endoplasmic reticulum (ER) stress. Human pancreatic islets were isolated by enzymatic digestion and density gradient purification from pancreatic samples of non-diabetic (ND; n = 17; age 65 ± 21 years; gender: 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 75 publications
(96 reference statements)
6
46
0
Order By: Relevance
“…Autophagy has been identified as an important player in beta cell survival and growth, contributing to cellular homeostasis and stress response [30]. While the role of autophagy in the context of type 2 diabetes has been studied extensively [31,32], its role in type 1 diabetes is relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has been identified as an important player in beta cell survival and growth, contributing to cellular homeostasis and stress response [30]. While the role of autophagy in the context of type 2 diabetes has been studied extensively [31,32], its role in type 1 diabetes is relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…mTor senses nutrient availability and regulates cell homeostasis, and it has been suggested that its loss impairs β-cells homeostasis as well as insulin sensitivity in peripheral tissues [27]. Among the intracellular processes controlled by mTor, autophagy as gained attention as a possible player in the survival of pancreatic β-cells with conflicting data showing, in different experimental models, pro-or antiapoptotic effects of an increased activation of autophagic pathways [28][29][30]. In our model, the recovered prosurvival profile was paralleled by decreased expression of the autophagic marker LC3-II, supporting the hypothesis of a negative impact of a disproportionated activation of autophagic pathways on cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and visceral fat are probably the main risk factors for T2D [9] and are involved in its pathophysiology as well as inflammation and insulin resistance [21]. Moreover, a study evaluating T2DM patients reported that obese subjects present higher levels of PGRN [13]. Taking in consideration the fact that BMI is a simple index of weight-for-height that is commonly used to classify overweight and obesity in adults, this study agreed with our finding revealing a significant difference of BMI between diabetic and control groups with significant positive correlation with PGRN.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is the major mechanism involved in the degradation and recycling of intracellular components, and its alterations have been proposed to cause beta cell dysfunction [13]. However, autophagy may be enhanced under a variety of atrophic conditions, as shown by the expression of several proteins involved in lysosomal degradation, including LC3 [14].…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%